Impacts of river flooding on urban agglomerations: a climate-impact analysis and the role of strategic planning for the Ruhr, Germany. Issue 2 (1st March 2022) - Kirstein, Madeleine; Schaefer, Mathias; Schnittfinke, Tanja; Greiving, Stefan; Küsters, Rouven
Abstract : In order to reveal the present and future flooding impacts on residential and mixed-use areas, a parallel modelling approach (PMA) was carried out. With the use of geo-information systems (GIS), temporal and spatial impacts can be quantified and visualised, while the results of the proposed method justify adequate regional planning strategies for the Ruhr, Germany. As an information system which is regularly updated within a cooperation process between the municipalities concerned, the so called ruhrFISְ of the Ruhr Regional Association (RVR) seems to be a promising approach to improve the evidence basis for adaptation actions.